Pengaruh Emisi Kendaraan Terhadap Kandungan Logam Timbal (Pb) Tanah dan Bulir Padi pada Lahan Sawah di Kecamatan Tebas Kabupaten Sambas - Rinto Manurung; Shenny Oktoriana; Anita Suharyani (School of Postgraduate Studies, Diponegoro Univer, 2023)
Lead (Pb) is one of most toxic pollutants. The main sources of Pb comes from industrial and vehicle gases. Lead contained in gas from vehicle will be absorbed and accumulated in the soil. Leads in the soil, especially in paddy soil alongside highway with many vehicles have a potential to be absorbed and accumulated in the grain. Solubility of Pb in the soil affecting the absorption of paddy is controlled by soil properties such as texture, organic matter, pH and cation exchange capacity. The research aims to study the effect of vehicle emission on Pb content in the soil, soil properties that influences the presences of Pb in the soil and its accumulation in grain. The research was conducted in paddy soil located alongside the highway of Sambas Regency as a rice producing center in West Kalimantan. Distance of soil and grain samplaing from the road will be used as a treatment to observe the effect of vehicle emission on Pb content, ie 0 – 50 meters, 50 – 100 meters and more than 100 meters. Soil samples were taken at 0-20 cm and 20-50 cm depth. Soil samples and grains are destracted by using nitric acid, hydrogen peroxide and perchloric acid. Furthermore, Pb content was measured using Atomic Absorbtion Spectrophotometry (AAS). The results showed that there is no effect of land distance from the road to the soil content. The average Pb content at 0-50 m, 50-100 m and more than 100 m at a depth of 0-20 cm were 29,62 ppm, 31,57 ppm and 35,03 ppm, respectively. While the average Pb content at a depth of 20-50 cm, respectively, were 27,16 ppm, 32,53 ppm and 35,97 ppm. The presence of Pb in the soil is significantly correlated with sand and clay fraction. The content of Pb on grains is above the tolerance limit (0,5 ppm) of Pb content in food, fruits and vegetables. Pb content is from 2,07 ppm to 5,10 ppm.